P98 Cervical TB lymphadenitis: A predominantly right-sided phenomenon due to ascending infection from the thorax. (14th November 2013) - Cresswell, FV; Vijayakumar, B; John, L; Davidson, RN
Abstract : Introduction: Cervical Tuberculous (TB) Lymphadenitis is the commonest presentation of extrapulmonary TB. There is however little evidence about its aetiology; consensus is divided as to whether it arises from infection via the pharyngeal lymphoid ring or from thoracic infection. Our clinical suspicions were that it is most frequently a right-sided phenomenon as a result of Mycobacterium Tuberculosis ascending the right paratracheal chain following pulmonary inoculation. Methods: We explored this hypothesis by retrospectively reviewing 211 cases of cervical TB lymphadenitis diagnosed at Northwick Park Hospital in London. We assessed clinical findings, neck ultrasound findings, chest radiograph findings and explored the literature to see what other evidence exists to support or refute this hypothesis. Results: Clinical assessment found that 62.1% (P < 0.0001) cases had right-sided disease, 28.9% left-sided and 9.0% bilateral. Of the 153 ultrasound scans available, 62% showed supraclavicular lymphadenitis (levels IV&V nodes) and only 9.5% submental/submandibular lymphadenitis (level I nodes). 205 chest x-rays were studied, the most frequent abnormality was lymphadenopathy (40/205), including 25 paratracheal lymphadenopathy (23/25 right-sided). Notably, 22/23 patients with right paratracheal lymphadenopathy had right-sided cervical lymphadenitis. Discussions: Our findings suggest that ascending infection from the thorax via the paratracheal chain following pulmonary inoculation plays the greatest role in the aetiology of cervical lymphadenitis. We explain this using anatomical studies. Infection via the pharynx may be implicated in those exhibiting upper cervical lymphadenitis. In some low-resource setting where TB may be diagnosed on clinical grounds alone, knowledge that right-sided supraclavicular nodes are the most frequently affected may add confidence to clinical decision-making.